STRUCTURAL DESIGN CARGO BERTH IN THE PORT OF LEBITI, TOJO UNA-UNA REGENCY, CENTRAL SULAWESI PROVINCE - Yola Aulia Loe, Priscilla
Maritime transport has a very important role for archipelagic countries, especially in improving the country's economy. Indonesia is the largest archipelagic country in the world with up to 17,508 islands. As an archipelagic country, Indonesia must be able to utilize the maritime transport sector as much as possible. Lebiti is one of the villages with a great potential in maritime transport located in Togean District, Tojo Una-Una Regency, Central Sulawesi Province, Indonesia. The construction of the port in Lebiti serves as the development of facilities to support local economic development and pave the way for transportation of general cargo for the citizens. The construction of Lebiti Port is planned as a local feeder port in Tojo Una-Una Regency, Central Sulawesi Province which serves domestic ocean transportation activities and as a destination for passengers and goods. The method used in planning the jetty deck on pile type berth structure consists of processing secondary data, calculating the load of the berth structure, designing the berth and trestle structure, modelling and analyze the structure, designing the reinforcement of the structural elements of the pier, and analyze the soil bearing capacity. The initial stage of the design is the collection and processing of environmental data, such as the tides, currents, winds, waves, and soil. Operational data processing is also carried out to obtain the load on the berth structure. Preliminary design is carried out to obtain the minimum cross-sectional dimensions required based on the initial calculation. The cross-sectional dimensions are modeled on the SAP2000 software. The results of the modelling will obtain the value of the unity check ratio (UCR), the deflection of the structure, the forces in the beams and slabs, as well as the reaction to the placement of the piles. The unity check ratio (UCR) value needs to be in the range of 0.7 to 1.0 in order to be in optimum conditions, and the deflection value must meet the design criteria used. The internal structural forces in the optimized design are used to design reinforcements of the structural elements. The analysis of the bearing capacity of the soil is conducted to obtain to calculate the required piling depth based on the soil bearing capacity so that the structure can withstand the load based on the reaction of the pile placement obtained from the modelling. The design of the berth structure in this Final Project refers to existing standards, including the Technical Standards and Commentaries for Port and Harbour Facilities in Japan published by The Overseas Coastal Area Development Institute of Japan (OCDI) in 2009, British Standard (BS), and Standar Nasional Indonesia (SNI), American Institute of Steel Construction (AISC) standard, American Concrete Institute (ACI) standard, American Society of Civil Engineers (ASCE) standard, American Association of State Highway and Transportation Officials (AASHTO) standard, and other valid supporting standards and product catalogues. The final result of the design strukture of the berth in this final project is the dimensions of the pier and trestle structures, the dimensions of the structural elements, and the dimensions and depth of pile driving.